Community service rehabilitation therapists' understanding of social accountability - Ntandoyenkosi L. Msomi; Andrew J. Ross (AOSIS, 2024)
Background: Social accountability is the obligation of health care providers to address the priority health concerns of the community they serve and of universities to ensure that graduates understand these social responsibilities. Although social accountability can combat systemic health inefficiencies, it is not well-understood or practised. Aim: The study aimed to explore community service rehabilitation therapists' understanding of social accountability. Setting: The study was conducted in KwaZulu-Natal, South Africa. Methods: This study used an interpretive exploratory design and purposively recruited 27 community service rehabilitation therapists namely, audiologists, speech-language therapists, occupational therapists, and physiotherapists working in public sector health facilities in rural and peri-urban areas. Four focus group discussions and four free attitude interviews were conducted, the results being thematically analysed. Results: Despite most of the participants not being instructed in social accountability as part of their formal training or institutional induction, three themes emerged based on their experiences. These themes include describing social accountability, values of social accountability, and values of community-based rehabilitation applicable to social accountability. Conclusion: Inclusion of instruction on social accountability as part of their formal training and health facility induction would contribute to rehabilitation therapists' understanding of social accountability. Contribution: The study contributes to data on rehabilitation education and community service training regarding social accountability within a South African context and has captured how experiences gained during community service contribute to the rehabilitation therapists' understanding of social accountability.